Kontestasi Memori dalam Novel Tiba Sebelum Berangkat Karya Faisal Oddang - Jati, Galih Pangestu; Rokhani, Umilia; Bagaskara, Akbar (Universitas Andalas, 2024)
This study aims to determine the discourse of memory contestation in the novel Tiba Sebelum Berangkat by Faisal Oddang. This cannot be separated from the relationship between memory and the formation of a person's identity. By using qualitative research methods, this study is divided into three stages, namely data collection, data analysis, and presentation of research results. Data collection is carried out by repeated reading of various data related to formal objects and material objects. Meanwhile, data analysis is carried out by looking for relationships between data to achieve a unity. The theory used is the social theory of remembering developed by Barbara Misztal. The results of the study are the existence of collective memory contestation that causes the identity of a person or group of people to experience a crisis. As a result, the individual commits various sexual deviations as a projection of the crisis.